2020
DOI: 10.1055/a-1190-5987
|View full text |Cite
|
Sign up to set email alerts
|

The S2-Alar-Iliac Screw for Pelvic Trauma

Abstract: Percutaneous sacro-iliac screw osteosynthesis is considered to be standard of care for most posterior pelvic ring fractures. However, special situations require alternative strategies for sufficient stabilization. In these cases, stabilization can often be achieved using posterior instrumentation e.g. using SIPS-screws (spina-iliaca-posterior-superior screws). However, this often leads to implant-related aggravation of the sometimes already critical soft tissue conditions after pelvic trauma. S2-Ala-Ilium scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Recently, there have been several reports on a technique of complete fixation in the pelvis for sacral fractures in FFP, avoiding spinopelvic fixation. These techniques are suitable for elderly patients, combining the S1 pedicle screw with the S2-alar-iliac screw or iliac screw for strong fixation in the pelvis [9] , [10] . However, there has been no report of its application to patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports on a technique of complete fixation in the pelvis for sacral fractures in FFP, avoiding spinopelvic fixation. These techniques are suitable for elderly patients, combining the S1 pedicle screw with the S2-alar-iliac screw or iliac screw for strong fixation in the pelvis [9] , [10] . However, there has been no report of its application to patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbopelvic fixation in combination with a transiliac-transsacral screw resulted in the least amount of motion [23]. However, the used S1/S2 ala-ilium screws technique in this study was restricted to sacral fixation, without including the lumbar spine, as described elsewhere [12]. The S1/S2 ala-ilium screws were significantly superior in terms of cycles to failure, corresponding failure load, and initial axial stiffness compared to the posterior SI screw alone and to the SI screw plus supra-acetabular external fixator.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner et al [28] demonstrated in their biomechanical study simulating a symphyseal and unilateral sacroiliac joint disruption in synthetic pelvises that a standard two-bar external fixation did not apply any compression across the sacroiliac joint. In a clinical study, the minimally invasive S2 ala-ilium screw fixation has been described as a successful treatment option for pelvic trauma [12]. This technique might be a successful treatment option for FFP type IIc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the S2AI screw technique has been widely used in spinal surgery, its applicability to pelvic fractures is largely unknown. Only a small number of clinical studies 14–17 have applied S2AI screws to pelvic fractures, and there have been no reports of related biomechanical studies. For sacral fractures with stable lumbosacral joints (Isler type I), the purpose of surgery is only to resolve the pelvic instability, and thus the lumbar spine does not need to be fixed 2 .…”
Section: Introductionmentioning
confidence: 99%